Assistance for women's development from national agencies. - Baxamusa, Ramala M.; Subramanian, Hema.; Gupte, Girija; Joshi, Shobha; Shreemati Nathibai Damodar Thackersey Women's University. Research Centre for Women's Studies (Bombay Popular Prakashan, 1992)
Compiled by Research Centre for Women's Studies, SNDT Women's University.
v. 1. Employment programmes / Ramala M. Baxamusa, Hema Subramanian -- v. 2. Housing programmes / Ramala M. Baxamusa, Girija Gupte -- v. 3. Development programmes / Ramala M. Baxamusa, Shobha Joshi.
Keywords: Women in development -- India; Women -- Government policy -- India; Women -- Employment -- Government policy -- India; Women -- Housing -- Finance -- Government policy -- India; Mortgages -- India; Housing policy -- India